2020
DOI: 10.1121/10.0001099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bilateral cochlear implants on vocal control

Abstract: Receiving a cochlear implant (CI) can improve fundamental frequency (F0) control for deaf individuals, resulting in increased vocal pitch control. However, it is unclear whether using bilateral CIs, which often result in mismatched pitch perception between ears, will counter this benefit. To investigate this, 23 bilateral CI users were asked to produce a sustained vocalization using one CI, the other CI, both CIs, or neither. Additionally, a set of eight normal hearing participants completed the sustained voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It is not clear whether CI users can incorporate auditory feedback with feedforward plans to monitor their speech output. A recent study 70 showed that CIs might help their user to refine their internal motor commands, but voice pitch monitoring might not happen regularly. The main message of the current study is that a high auditory sensitivity does not guarantee a successful error correction in an ongoing vocalization.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is not clear whether CI users can incorporate auditory feedback with feedforward plans to monitor their speech output. A recent study 70 showed that CIs might help their user to refine their internal motor commands, but voice pitch monitoring might not happen regularly. The main message of the current study is that a high auditory sensitivity does not guarantee a successful error correction in an ongoing vocalization.…”
Section: Future Directionsmentioning
confidence: 99%
“…The detrimental effect of using CIs on voice quality is different than what has been seen for fundamental frequency and intensity control. Kirchner et al 8 measured bilateral CI users’ ability to maintain a stable fundamental frequency when producing a sustained vowel while either using or not using their CIs. Unlike with voice quality, they did not find a significant shift in fundamental frequency control when the CI was on versus off.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of CIs on various aspects of vocal production in CI users remains unclear. For instance, although there is evidence that access to auditory feedback through CIs could improve vocal pitch control 5 , 6 , such effects are not consistent across studies (e.g., 7 , 8 ). To date, it has been difficult to predict a consistent pattern of vocal characteristics for CI users (e.g., 7 , 9 , 10 ), and the prevalence of voice disorders within CI users is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a total of eight stimuli, each consisting of a vocalization of /a/ collected in a previous study ( Kirchner et al , 2020 ). Multiple vocalizations, recorded from different speakers, were used in a random order to help participants maintain attention.…”
Section: Methodsmentioning
confidence: 99%